2003
DOI: 10.1183/09031936.03.00086002
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-sensitive rhinitis-associated changes in upper airway innervation

Abstract: Aspirin-sensitive rhinitis is the manifestation of aspirin intolerance in the upper respiratory tract. The disease represents a pseudoallergy against aspirin or related nonsteroidal anti-inflammatory drugs. As a major immunomodulatory role for airway innervation has been proposed in airway inflammatory diseases, the present study assessed changes in human nasal mucosa innervation in patients with aspirinsensitive rhinitis in comparison to a control group.Immunohistochemistry for protein gene product 9.5, tachy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…The disease is a pseudoallergy against aspirin and related nonsteroidal anti-inflammatory drugs. Immunohistochemical analysis demonstrated that aspirin-sensitive rhinitis patients also had a significant increase in VIP-immunoreactive nerve fibers (80). These changes observed for the different forms of chronic upper airway inflammation may be partly regulated via neurotrophins.…”
Section: Human Respiratory Sensory Innervationmentioning
confidence: 85%
See 2 more Smart Citations
“…The disease is a pseudoallergy against aspirin and related nonsteroidal anti-inflammatory drugs. Immunohistochemical analysis demonstrated that aspirin-sensitive rhinitis patients also had a significant increase in VIP-immunoreactive nerve fibers (80). These changes observed for the different forms of chronic upper airway inflammation may be partly regulated via neurotrophins.…”
Section: Human Respiratory Sensory Innervationmentioning
confidence: 85%
“…To assess if alterations in neuronal subpopulations are disease-specific or an epiphenomenon of the inflammation, different subtypes of chronic upper airway diseases including hyperreflectoric rhinitis (36), aspirin-sensitive rhinitis (80) and toxic rhinitis (62) have been examined. Hyperreflectoric rhinitis is a chronic upper airway inflammatory disease related to a nonspecific hyperreactivity.…”
Section: Human Respiratory Sensory Innervationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the potential role in drug therapy, the transporters also transport peptide fragments and may scavenge peptide from the oropharyngeal cavity back into the systemic circulation. In this respect, it has been shown that numerous neuropeptides are up-regulated in different states of upper airway inflammation such as toxic rhinitis [38], intermittent seasonal allergic rhinitis [39], perennial allergic rhinitis [40], aspirin-sensitive rhinitis [41] or hyperreflectoric rhinitis [42]. Also, the transporters may function as uptake system for neurotrophin or tachykinin fragments [43,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether changes in neuronal populations are disease-specific or an epiphenomenon of inflammation the different rhinitis forms have been examined for example hyperreflectoric rhinitis [12], aspirin-sensitive rhinitis [66] and toxic rhinitis [67].…”
Section: Role In Airway Inflammationmentioning
confidence: 99%